2011
DOI: 10.1007/jhep05(2011)017
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on 4D conformal and superconformal field theories

Abstract: We derive general bounds on operator dimensions, central charges, and OPE coefficients in 4D conformal and N = 1 superconformal field theories. In any CFT containing a scalar primary φ of dimension d we show that crossing symmetry of φφφφ implies a completely general lower bound on the central charge c ≥ f c (d). Similarly, in CFTs containing a complex scalar charged under global symmetries, we bound a combination of symmetry current two-point function coefficients τ IJ and flavor charges. We extend these boun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
484
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(510 citation statements)
references
References 94 publications
25
484
1
Order By: Relevance
“…6 This result rules out the existence of exotic (2, 0) theories with a central charge smaller than that of the A 1 theory. A much stronger conclusion follows if one accepts the standard bootstrap wisdom [59,60] that the crossing equation has a unique unitarity solution whenever a bound is saturated. We are then making the precise mathematical conjecture that for c ¼ 25 the CFT data contained in (1.3) are completely determined by the bootstrap equation.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 This result rules out the existence of exotic (2, 0) theories with a central charge smaller than that of the A 1 theory. A much stronger conclusion follows if one accepts the standard bootstrap wisdom [59,60] that the crossing equation has a unique unitarity solution whenever a bound is saturated. We are then making the precise mathematical conjecture that for c ¼ 25 the CFT data contained in (1.3) are completely determined by the bootstrap equation.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Indeed, this will be the reason that we can make progress in studying the conformal phase of (2, 0) SCFTs despite the absence of a conventional definition. Thus in broad terms this work will mirror many recent bootstrap studies [37][38][39]59,60,. We will not review the basic philosophy in any detail here.…”
Section: The Bootstrap Program For (2 0) Theoriesmentioning
confidence: 94%
“…9 Recall that in 6 − dimensions, the Lagrangian (1.1) has three fixed points that were refer to as the critical theory, Theory 2, and Theory 3. They correspond, respectively, to the red dot, the black dot close to the red dot, and the other black dot in Figure 2 of [55].…”
Section: Discussionmentioning
confidence: 99%
“…The seminal work [8] proposed an efficient numerical procedure for extracting information about the space of all conformal field theories, and has been followed by many other works in a variety of contexts [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Similarly, the studies [24][25][26][27] have shown that it is even possible to analytically derive completely generic constraints on the spectrum of CFTs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the studies [24][25][26][27] have shown that it is even possible to analytically derive completely generic constraints on the spectrum of CFTs. Numerical works have been possible due to increased computer power in the last decades, and rely crucially on an increased understanding of conformal blocks -see [15,[28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%